2021
DOI: 10.1016/j.ejca.2021.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 among the staff and patients of a French cancer centre after first lockdown: The canSEROcov study

Abstract: Background In view of the potential gravity of SARS-CoV-2 infection for patients with cancer, epidemiological data are vital to assess virus circulation among patients and staff of cancer centres. We performed a prospective study to investigate seroprevalence of SARS-CoV-2 antibodies among staff and cancer patients at a large cancer centre, at the end of the period of first national lockdown in France, and to determine factors associated with the risk of SARS-CoV-2 infection. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 44 publications
(47 reference statements)
6
19
0
Order By: Relevance
“…However, in our population of cancer patients, diarrhea was reported in 21.4% of COVID+ cases and in 4% of COVID-; similarly for the HCWs, these figures were 31.5 and 13.7%, respectively. These data were in accordance with what has been observed in the literature, with gastrointestinal incidence (mainly diarrhea) ranging from 4 to 50% of cases [27,41].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, in our population of cancer patients, diarrhea was reported in 21.4% of COVID+ cases and in 4% of COVID-; similarly for the HCWs, these figures were 31.5 and 13.7%, respectively. These data were in accordance with what has been observed in the literature, with gastrointestinal incidence (mainly diarrhea) ranging from 4 to 50% of cases [27,41].…”
Section: Discussionsupporting
confidence: 93%
“…Studies reporting associations between seroprevalence and self-reported symptoms for healthcare workers (HCWs) found that fever, malaise, and fatigue were especially common alongside anosmia and ageusia [ 25 , 26 ]. However, little is known about HCWs from oncology departments and cancer centers despite the fact that they have been a under major strain during the pandemic [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the start of SARS-CoV-2 epidemic, it soon became clear that patients with cancer represent a very vulnerable population with a high risk of severe COVID-19 and a high mortality rate [ 12 , 13 , 17 21 ]. For this reason, both the oncological and hematological societies recommend constant and careful screening to identify and isolate SARS-CoV-2 infected patients, avoiding infection spreading among this very frail population [ 22 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario the management of cancer patients underling antineoplastic therapy remains very challenging [ 9 15 ]. Furthermore, in patients with solid and hematological tumors, a clinical anamnestic screening by specific triage alone may not be appropriate to intercept SARS-CoV-2 infection cases since some of the symptoms of malignancy may be similar as those of SARS-CoV-2 infection [ 16 , 17 ]. For this reason, it is important, in cancer populations, especially in the outpatient setting, to define the most effective and targeted monitoring strategies in order to detect, as accurately as possible, the prevalence of SARS-CoV-2 infection in a definite temporal context and geographical area.…”
Section: Introductionmentioning
confidence: 99%